‘In the dark’: parents’ lifelong commitment to supporting children with Bardet-Biedl syndrome - Jeanette Ullmann Miller; Lena Fauske; Solrun Sigurdardottir; Shahrzad Arfa; Charlotte von der Lippe (Health Psychology and Behavioral Medicine)
Background Bardet-Biedl syndrome (BBS) is a rare disorder involving a complex combination of eye and kidney diseases, obesity and learning difficulties. To better understand the roles of family caregivers, this study sought to explore parents’ experiences of supporting adult children with BBS.Method This study included 17 parents of adult children with BBS. Semi-structured interviews were used as the research method. The generated data were interpreted using a reflexive thematic analysis, which employed a phenomenological and hermeneutical approach.Result Four themes were identified – namely, worries and expectations for the child's future, advocate and companion, in the power of the health and support system, and sources of support and coping. The findings indicate that the parents’ everyday lives are affected in many ways by caring for adult children with BBS.Conclusion This study highlights the various roles and responsibilities of parents of adult children with BBS, including advocating for health services and attempting to fill gaps in care and social relationships. Hence, the findings of this study provide valuable insights for health professionals and support systems, helping to identify key areas for future initiatives aimed at better addressing the needs of adults with BBS and their parents.